Antiproliferative effect of apocynin in cervical epithelial cells infected by HPV 16 involves change of ROS production and cell cycle - Lima, Natalia Alves; Scharf Santana, Natalia de Carvalho; Alves de Lima, Nayara Cristina; Lazarin-Bidoia, Danielle; Bonfim-Mendonca, Patricia de Souza; Nakamura, Tania Ueda; Nakamura, Celso Vataru; Lopes Consolaro, Marcia Edilaine; Ximenes, Valdecir Farias [UNESP]; Silva, Sueli de Oliveira (Springer, 2017)
The cervical cancer is characterized as a public health problem. The human papillomavirus, especially the high-risk types 16 and 18, is present in 99.7% of cases of invasive cervical cancers. Due to high prevalence, the search for new drugs for the treatment is continuous. The apocynin, compound belonging to the class of catechol-methoxy acetophenone, has been used as an effective and non-toxic inhibitor of the NADPH oxidase complex, in many experimental models. Some early studies have indicated that apocynin also exerts antiproliferative activity inducing cell death by apoptosis. Thus, we evaluated the effect of apocynin in cervical epithelial cells infected by human papillomavirus 16 (SiHa cells) by analyzing oxygen species production, cell cycle, cell morphology, cell volume, membrane integrity and mitochondria membrane potential. Our data showed that apocynin induces antiproliferative effects by decreasing reactive oxygen species production and inducing cell cycle arrest, activating pathways that induce apoptosis cell death.
Keywords: SiHa; HPV 16; Apocynin; Reactive oxygen species